Poly (ADP-ribose) Interacts With Phosphorylated α-Synuclein in Post Mortem PD Samples - Puentes, Laura N.; Lengyel-Zhand, Zsofia; Lee, Ji Youn; Hsieh, Chia-Ju; Schneider, Mark E.; Edwards, Kimberly J.; Luk, Kelvin C.; Lee, Virginia M.-Y.; Trojanowski, John Q.; Mach, Robert H. (Frontiers in Aging Neuroscience, 2021)
Poly (ADP-ribose) (PAR) is a negatively charged polymer that is biosynthesized by Poly (ADP-ribose) Polymerase-1 (PARP-1) and regulates various cellular processes. Alpha-synuclein (αSyn) is an intrinsically disordered protein (IDP) that has been directly implicated with driving the onset and progression of Parkinson’s disease (PD). The mechanisms by which αSyn elicits its neurotoxic effects remain unclear, though it is well established that the main components of Lewy bodies (LBs) and Lewy neurites (LNs) in PD patients are aggregated hyperphosphorylated (S129) forms of αSyn (pαSyn). In the present study, we used immunofluorescence-based assays to explore if PARP-1 enzymatic product (PAR) promotes the aberrant cytoplasmic accumulation of pαSyn. We also performed quantitative measurements using in situ proximity ligation assays (PLA) on a transgenic murine model of α-synucleinopathy (M83-SNCA*A53T) and post mortem PD/PDD patient samples to characterize PAR–pαSyn interactions. Additionally, we used bioinformatic approaches and site-directed mutagenesis to identify PAR-binding regions on αSyn. In summary, our studies show that PAR–pαSyn interactions are predominantly observed in PD-relevant transgenic murine models of αSyn pathology and post mortem PD/PDD patient samples. Moreover, we confirm that the interactions between PAR and αSyn involve electrostatic forces between negatively charged PAR and lysine residues on the N-terminal region of αSyn.